Comparing the Cost of Fandom in European Football - ÖZAYDIN, SELÇUK; TINAZ, CEM (Taylor and Francis, 2022)
Undoubtedly, fans are an essential factor of success for football clubs due to their potential to generate income and contribute to the home-field advantage. So far, the literature has focused on fans’ contribution to their teams; however, the cost of being a fan has not been investigated thoroughly. The increasing commercialization of football has emphasized football consumption as a commodity, which improved the overall quality of the produced output. A fan has to pay more than the previous year to show their affiliation to their beloved team every year. Especially with the global pandemic and its adverse effects on disposable income and employment, being a fan will be costlier more than ever. This chapter examines the cost of being a football fan for selected teams from the Big 5 leagues of Europe, Portuguese Primeira Liga and the Turkish Super League. We examine the cost, both in absolute terms and as a percentage of GDP per capita and minimum wage and identify the fan-friendly ones among Europe’s top teams in terms of cost. © 2022 selection and editorial matter, Danielle Sarver Coombs and Anne C. Osborne; individual chapters, the contributors.
▪ Book: Routledge Handbook of Sport Fans and Fandom.